Konsep Pendidikan Dalam Misi Kerasulan Muhammad Saw: Analisis QS Al-Baqarah:2/ 151. - Sarmilah Amir (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
Modern education today tends to focus solely on intellectual academic achievement, often neglecting the development of character and spiritual intelligence. Furthermore, there have not been many studies that systematically integrate the prophetic educational model with contemporary parenting theories. This study aims to analyze the concept of education in the prophetic mission of the Prophet Muhammad, peace be upon him, based on Quranic Surah Al-Baqarah 2:151, as well as its relevance to modern parenting styles. This qualitative study, employing a library research approach, uses the tahlili method to systematically interpret the verse. The analysis was conducted through linguistic (lughawi) analysis, examination of the verse’s contextual relationships (munāsabah), and interpretations by classical and contemporary exegetes. The results of the study indicate that the concept of education in the prophetic mission encompasses three main aspects: tilāwah (recitation of verses and setting a good example), tazkiyah (purification of the soul and morals), and ta‘līm (the gradual teaching of knowledge and wisdom). These three concepts demonstrate that the Prophet Muhammad’s (peace be upon him) approach to education was holistic, encompassing spiritual, intellectual, moral, and social development. This study also found that this concept is highly relevant to authoritative parenting—a democratic parenting style that balances affection, firmness, two-way communication, and leading by example in raising children. Thus, the concept of education in the mission of the Prophet can serve as a proactive and solution-oriented model of Islamic education in addressing the challenges of child-rearing in the modern era.